ANALYSIS OF FAILURE FACTORS IN RUNNING LED CIRCUIT ASSEMBLY USING BREADBOARD AND PCB AMONG VOCATIONAL ELECTRONICS ENGINEERING STUDENTS - M Fachrie Al Faridzi; Zidni Ma'ruf; Abi Al-Hukmi; M Julian Jaya (Universitas Lampung, 2026)
Running LED circuit assembly is a widely implemented introductory practicum module in vocational electronics engineering education, yet students consistently encounter operational failures during assembly activities using both breadboard and PCB media. This study aimed to analyze the dominant failure factors in running LED circuit assembly and compare operational failure tendencies between breadboard and PCB media among vocational electronics engineering students. A quantitative descriptive survey was conducted using a five-point Likert-scale questionnaire distributed to 50 students at Sriwijaya State Polytechnic. Results indicated that in breadboard assembly, damaged components and IC overheating was the dominant failure factor (M = 3.54), followed by incorrect polarity installation (M = 3.30) and incorrect wiring (M = 3.24). In PCB assembly, broken copper traces and open circuit defects dominated (M = 3.62), followed by solder bridge defects and incorrect component placement (M = 3.50). Comparative analysis revealed that PCB assembly demonstrated a higher overall operational failure tendency than breadboard assembly, with mean scores of 3.10–3.18 versus 2.86–2.92 respectively. These findings suggest that breadboard failures are predominantly reversible and rooted in power mishandling, while PCB failures are largely permanent and driven by fabrication process execution. Practicum instruction should prioritize power supply verification for breadboard and etching process control for PCB assembly.